The Future of European Growth Policies: Resetting Integration - Nauro F. Campos (Intereconomics, 2016)
This note argues that one should lay the focus of future European growth policy on integration and technology. This focus should be on maximising the growth effects of their interaction, with an emphasis on the importance of deep integration. The note provides three examples that show how deep integration has contributed to stop the relative economic decline in the UK vis-à-vis the EU founding members; how deep integration increased productivity in Sweden, Austria, and Finland compared to that in Norway; and how a key mechanism to advancements in the new EU member states has been the capacity of deep integration to generate institutional change.
Keywords: 330